2012
DOI: 10.1055/s-0032-1314834
|View full text |Cite
|
Sign up to set email alerts
|

Allopregnanolone Alters the Luteinizing Hormone, Prolactin, and Progesterone Serum Levels Interfering with the Regression and Apoptosis in Rat Corpus Luteum

Abstract: Steroids synthesized in the central nervous system are termed "neurosteroids". They are synthesized and metabolized in several brain areas. The objective of this work was to determine if 1 intracerebroventricular allopregnanolone injection in rats can interfere in luteal regression in a close relationship with modifications in LH, progesterone, and prolactin serum concentrations. Allopregnanolone was injected during proestrus morning and the animals were sacrificed on oestrous morning. Ovulation test and histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…However, the short half‐life of allopregnanolone and other inhibitory neurosteroids serves as a hindrance to their efficacy in the treatment of anxiety. Furthermore, exogenous allopregnanolone has been shown to impair ovarian function in the rat , suggesting that there may be a need for alternative approaches to elevating neurosteroid levels. Synthetic analogues such as ganaloxone have shown sedative, anxiolytic and anticonvulsant effects .…”
Section: Steroid Hormonesmentioning
confidence: 99%
“…However, the short half‐life of allopregnanolone and other inhibitory neurosteroids serves as a hindrance to their efficacy in the treatment of anxiety. Furthermore, exogenous allopregnanolone has been shown to impair ovarian function in the rat , suggesting that there may be a need for alternative approaches to elevating neurosteroid levels. Synthetic analogues such as ganaloxone have shown sedative, anxiolytic and anticonvulsant effects .…”
Section: Steroid Hormonesmentioning
confidence: 99%
“…In fact, it is known that the concentration of ALLO and P4 varies during the estrous cycle and pregnancy in a similar manner. We have reported that intra-cerebroventricular (ICV) administration of ALLO modulates the hypothalamic-pituitary-gonadal axis and induces morpho-physiological changes at the ovarian level [15][16][17][18]. ALLO induces a reduction in nuclear proliferation cell antigen expression, accompanied by an increase in apoptosis of granulosa cells stimulating follicular atresia.…”
Section: Introductionmentioning
confidence: 99%
“…Control animals were injected with sterile saline with 1% propylene glycol. The 4.9 μ M concentration of the GABA A receptor antagonist bicuculline was the same used in our previous published results [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…We have previously demonstrated that the neuroactive steroids progesterone and ALLO modulate striatal dopaminergic activity of rats under different gonadal hormonal conditions [ 19 , 20 ] and that systemic administration of progesterone to hemiparkinsonian rats prevents depression-like behavior [ 21 ]. These beneficial premotor effects led us to inquire whether or not the neuroprotective effects of progesterone and/or its metabolite ALLO on premotor conditions could be extended to motor manifestations in a model of hemiparkinsonism in rats.…”
Section: Introductionmentioning
confidence: 99%